IMPROVING THE EFFICIENCY OF INNOVATIVE SERVICES IN THE DIGITAL ECONOMY - Mirzaev , Kulmamat (GREEN ECONOMY AND DEVELOPMENT, 2026)
This article examines the potential of using digital technologies for innovative development in the service sector. It also analyzes the internal potential for increasing the efficiency of innovative services in the context of our republic’s digital economy and provides scientific and practical justification for ways to achieve this.